2021
DOI: 10.18203/2394-6040.ijcmph20214553
|View full text |Cite
|
Sign up to set email alerts
|

Ocular manifestations in children with developmental delay in an eye hospital of northern Bangladesh

Abstract: Background: The aim of this study was to identify common ocular manifestations in children with developmental delay in an eye hospital of northern part of Bangladesh.Methods: It was a retrospective medical record review of children with developmental delay who attended the pediatric ophthalmology department in an eye hospital from January 2019 to December 2019. Data were collected for their age, gender, past medical history, ophthalmic examination findings and systemic problems. Ophthalmic examination included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
3
2
0
Order By: Relevance
“…Sixty three children (15.5%) presented with strabismus, esotropia being the predominant entity. Afroze R, 13 reported the prevalence of strabismus to be 22.5%, with esotropia (12.7%) being more common than exotropia (9.8%) which is in accordance with the study of Nielsen et al 17 Nystagmus was seen in 225 (55.4%) children. These children performed goal-directed hand movements slowly and with difficulty.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Sixty three children (15.5%) presented with strabismus, esotropia being the predominant entity. Afroze R, 13 reported the prevalence of strabismus to be 22.5%, with esotropia (12.7%) being more common than exotropia (9.8%) which is in accordance with the study of Nielsen et al 17 Nystagmus was seen in 225 (55.4%) children. These children performed goal-directed hand movements slowly and with difficulty.…”
Section: Discussionsupporting
confidence: 72%
“…This was in accordance with studies conducted by Smitha et al 12 Similarly, Afroze R, in a study conducted in Bangladesh found a preponderance of boys. 13 Very few studies are available for ocular manifestations under 5 years of age. Our study found maximum patients in the age group of 1 -2 years (42%), which follows similar studies conducted in Karnataka and Mumbai.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated the distribution and percentage of reduced VA, RE, strabismus and reduced contrast sensitivity in 257 DD children having IQ ≤ 80 by WISC, between the age ranges of 06-16 years, mean age was 8.88 ± 2.70 years. In our study, male children were more 160 (62.3%) than female 97 (37.7%), similar to the studies conducted by Smitha KS et al 15 and Afroze R et al 16 …”
Section: Discussionsupporting
confidence: 92%
“…14 We evaluated the distribution and percentage of reduced VA, RE, strabismus and reduced contrast sensitivity in 257 DD children having IQ ≤ 80 by WISC, between the age ranges of 06-16 years, mean age was 8.88 ± 2.70 years. In our study, male children were more 160 (62.3%) than female 97 (37.7%), similar to the studies conducted by Smitha KS et al 15 and Afroze R et al 16 Vora et al conducted a study on DD children and reported the prevalence of RE as 58.5%. The prevalence rates were 18.6%, 24.3% and 27.1% for hyperopia, myopia, and astigmatism respectively.…”
Section: Discussionsupporting
confidence: 90%